Conversion From Calcineurin Inhibitors to Mammalian Target of Rapamycin Inhibitors in Kidney Transplant Recipients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Zeng, Jun; Zhong, Qiang; Feng, Xiaobing; Li, Linde; Feng, Shijian; Fan, Yu; Song, Turun; Huang, Zhongli; Wang, Xianding; Lin, Tao (Frontiers in Immunology, 2021)
Background A systematic review and meta-analysis were performed to investigate the efficacy and safety of conversion from calcineurin inhibitors (CNIs) to mammalian target of rapamycin inhibitors (mTORi) in kidney transplant recipients (KTRs). Methods MEDLINE, EMBASE, PubMed, and Cochrane Library were searched to identify randomized controlled trials (RCTs) that compared the continuation of CNI with conversion to mTORi therapy. Results Twenty-nine RCTs (5,747 KTRs) were included in our analysis. Meta-analysis of the glomerular filtration rate (SMD 0.20; 95%CI 0.10–0.31; P<0.01) and malignancy (RR 0.74; 95%CI 0.55–0.99; P=0.04) demonstrated a significant advantage of mTORi conversion over CNI continuation. However, the risk of acute rejection (RR 1.58; 95%CI 1.22–2.04; P<0.01), infection (RR 1.55; 95%CI 1.01–1.31; P=0.04), proteinuria (RR 1.87; 95%CI 1.34–2.59; P<0.01), leukopenia (RR 1.56; 95%CI 1.27–1.91; P<0.01), acne (RR 6.43; 95%CI 3.43–12.04; P<0.01), and mouth ulcer (RR 11.70; 95%CI 6.18–22.17; P<0.01) were higher in the mTORi group. More patients in the conversion group had to discontinue study medication (RR 2.52; 95%CI 1.75–3.63; P<0.01). There was no significant difference between the two groups with regard to death, graft loss, diabetes, chronic allograft nephropathy, and interstitial fibrosis/tubular atrophy. Conclusions Posttransplant patients have a better graft function and lower incidence of malignancy after conversion from CNI to mTORi therapy. However, this conversion strategy may be prevented by the higher drug discontinuation rate due to mTORi-associated adverse events, such as more acute rejection, infection, proteinuria, leukopenia, acne, and mouth ulcer, indicating that conversion therapy may only be a treatment option in selected patients.